Time since targets’ initial public offerings, asymmetric information, uncertainty, and acquisition pricing - Jindra, Jan; Moeller, Thomas (Journal of Banking & Finance, 2020)
We document that acquirer announcement returns decrease and takeover premiums increase with the length of time since targets’ initial public offerings. Declining asymmetric information that leads to lower target valuation uncertainty for the acquirer can explain these effects. Newly public targets have greater information asymmetry (relative to their established counterparts) making their valuation more uncertain for a less-informed acquirer. Risk-averse acquirer managers pay less for riskier targets, resulting in lower takeover premiums and higher acquirer announcement returns. Over time, as the target builds a public track record, the asymmetric information about its valuation declines and takeover premiums increase to the benefit (detriment) of target (acquirer) shareholders.